The impact of the GLOSSY2 and GLOSSY2-LIKE BAHD-proteins in affecting the product profile of the maize fatty acid elongase - Alexander, Liza Esther; Winkelman, Dirk; Stenback, Kenna E.; Lane, Madison; Campbell, Katelyn R.; Trost, Elysse; Flyckt, Kayla; Schelling, Michael A.; Rizhsky, Ludmila; Yandeau-Nelson, Marna D.; Nikolau, Basil J. (Frontiers in Plant Science, 2024)
The maize glossy2 and glossy2-like genes are homologs, which encode proteins that belong to the BAHD family of acyltransferases. In planta genetic studies have demonstrated that these genes may be involved in the elongation of very long chain fatty acids (VLCFAs) that are precursors of the cuticular wax fraction of the plant cuticle. VLCFAs are synthesized by a fatty acyl-CoA elongase complex (FAE) that consists of four component enzymes. Previously, we functionally identified the maize FAE component enzymes by their ability to complement haploid Saccharomyces cerevisiae strains that carry lethal deletion alleles for each FAE component enzyme. In this study we used these complemented haploid strains and wild-type diploid strains to evaluate whether the co-expression of either GLOSSY2 or GLOSSY2-LIKE with individual maize FAE component enzymes affects the VLCFA product-profile of the FAE system. Wild-type diploid strains produced VLCFAs of up to 28carbon chain length. Co-expression of GLOSSY2 or GLOSSY2-LIKE with a combination of maize 3-ketoacyl-CoA synthases stimulated the synthesis of longer VLCFAs, up to 30-carbon chain lengths. However, such results could not be recapitulated when these co-expression experiments were conducted in the yeast haploid mutant strains that lacked individual components of the endogenous FAE system. Specifically, lethal yeast mutant strains that are genetically complemented by the expression of maize FAE-component enzymes produce VLCFAs that range between 20-and 26carbon chain lengths. However, expressing either GLOSSY2 or GLOSSY2-LIKE in these complemented strains does not enable the synthesis of longer chain VLCFAs. These results indicate that the apparent stimulatory role of GLOSSY2 or GLOSSY2-LIKE to enable the synthesis of longer chain VLCFAs in diploid yeast cells may be associated with mixing plant enzyme components with the endogenous FAE complex.